RUMUSAN SISTEM PENDIDIKAN YANG ISLAMI - Ali Mubin (Universitas Muhammadiyah Tangerang, 2020)
This research is motivated by several reasons, including, First, at this time there was a philosophical error that was applied by educational institutions that is generally education in Indonesia is influenced by Western paradigms that tend to be secular. Second: it is time for Muslims to apply educational principles based on Islamic teachings that originate from the Koran and Sunnah. The writing method uses a descriptive analytical method that is philosophical normative that is adjusted to the sources of literature. The results of the study can be mentioned that the formulation of Islamic education is education that bases its conception on the teachings of monotheism, namely efforts to streamline the application of Islamic religious values that can lead to the transformation of values and knowledge as a whole to humans, society and the world in general in accordance with values which is transcendental